Who reaches the NHL? A 20-year retrospective analysis of junior and adult ice hockey success in relation to biological maturation in male Swedish players - Niklasson, E.; Lindholm, O.; Rietz, M.; Lind, J.; Johnson, D.; Lundberg, T. R. (Sports Medicine, 2024)
Objectives: This study investigated the relationship between biological maturation and success in adolescence and adulthood in male Swedish ice hockey players. Methods: Anthropometric records of players in certified ice hockey high schools between 1998 and 2017 were retrieved (n = 4787). The database was complemented with records of Swedish junior national teams (U16, U18, U20) and National Hockey League (NHL) appearances. Biological maturation was recorded as a percentage of adult height (%AH), and selection probabilities were estimated using a generalised linear mixed effects model. Biological age was determined by comparing players with age-matched growth reference values. Categories of %AH, standard deviation z-scores and biological age offset describing early, on-time and late maturation were created. Results: A total of 217 players had played on the U16 national team (junior success), and 96 reached the NHL (adult success). The difference [95% confidence interval (CI)] in baseline %AH between players with junior versus adult success was - 0.75 (- 0.39, - 1.11). Looking at age-offset categories in junior success, 30% of players were early maturing and 19% of players were late maturing, showing a bias towards early maturation (p < 0.01). In contrast, more late-maturing players (40%) achieved adult success than early-maturing players (25%), and NHL players had significantly later maturation [%AH: - 0.48 (- 0.80, - 0.16)] than non-NHL players. Conclusion: This unique 20-year analysis shows that junior success in male ice hockey is positively related to early maturation, while adult success is inversely related to advanced maturation. Ice hockey organisations should implement maturation assessments to optimise the development of both late- and early-matured players.